Tracking SARS-CoV-2 Variants Using a Rapid Typification Strategy: A Key Tool for Early Detection and Spread Investigation of Omicron in Argentina - Castro, Gonzalo M.; Sicilia, Paola; Bolzon, María Laura; Lopez, Laura; Barbás, María Gabriela; Pisano, María Belén; Ré, Viviana E. (Frontiers in Medicine, 2022)
SARS-CoV-2 variants of concern (VOC) and interest (VOI) present mutations in reference to the original virus, being more transmissible. We implemented a rapid strategy for the screening of SARS-CoV-2 VOC/VOIs using real time RT-PCR and performed monitoring and surveillance of the variants in our region. Consecutive real-time RT-PCRs for detection of the relevant mutations/deletions present in the Spike protein in VOC/VOIs (TaqMan™ SARS-CoV-2 Mutation Panel, Applied Biosystems) were implemented. A total of 6640 SARS-CoV-2 RNA samples (Cts<30) from infected individuals in Central Argentina during 2021 were analyzed using different algorithms that were gradually adapted to the changing scenarios of local variant circulation. The strategy developed allowed the early detection and the identification of VOC/VOIs that circulated through the year, with a 100% of concordance with the WGS. The analyses of the samples showed introductions of VOCs Alpha and Gamma in February and March 2021, respectively. Gamma showed an exponential increase, with a peak of detection in July (72%), being responsible of the second wave of COVID19 in Argentina. Since VOC Delta entered into the region, it increased gradually, together with VOI Lambda, replacing VOC Gamma, until being the main variant (84.9%) on November. By December, these variants were replaced by the emergent VOC Omicron in a term of a two weeks, producing the third wave. We report a useful tool for VOC/VOI detection, capable to quickly and cost-effectively monitor currently recognized variants in resource-limited settings, which allowed to track the recent expansion of Omicron in our region, and contributed to the implementation of public health measures to control the disease spread.